OPTIMISING PUBLIC HEALTH OPEX: A CONCEPTUAL SYSTEMATIC REVIEW OF HEALTH SECTOR AND RURAL DEVELOPMENT STAKEHOLDER MANAGEMENT IN KENYA - Okore, Lavender; Qorri, Dejsi; Owuor, Patrick; Kovács, Krisztián; Molnár, Prof. Edina (Applied Studies in Agribusiness and Commerce, 2025)
The African Health ecosystem is yet to optimize multi-stakeholder collaborative efforts for desired outcomes in health-care interventions. Despite heavily relying on multiple sectors and developing progressive engagement frameworks, challenges in harnessing diverse stakeholder contributions to meet evolving health-care priorities persist within the sector. This situation exacerbates the challenge of health disparities, especially regarding regional and rural development. We seek to focus on Reversing the Hierarchical Overview of Public Health Stakeholders in Kenya by redesigning it to fit - a community and related stakeholders-centred Approach. We used the Conceptual Systematic Review to conceptualize the complexity of stakeholders’ ecosystem coordination. We use peer-reviewed literature and reports covering the stakeholders in public health.  We coded the literature findings following the CSR stages. The study develops a proposed ecosystem map of stakeholders that incorporates suggested changes for improved local stakeholders’ coordination and local ownership of health investment activities in Kenya. The structuring and layering of the stakeholders will be informed by the tenets of the stakeholder salience model, thus advancing theoretical discourse in the area.